Modelling the Impact of Global Financial Crisis on the Indian Stock Market through GARCH Models. (March 2016) - Mathur, Shreya; Chotia, Varun; Rao, N.V.M.
The purpose of this article is to examine the impact of Global Financial Crisis on the Indian stock market which has been an issue of immense interest to time series analysts and econometricians around the world. We have conducted empirical analysis on daily stock returns of the top 20 companies listed on Bombay Stock Exchange (BSE) for the period 2001–2012. The study shows the presence of autoregressive conditional heteroskedasticity (ARCH) effect and volatility clustering during the study period. The BSE Sensex also depicts asymmetric volatility effect. Therefore, the standard generalised autoregressive conditional heteroskedasticity (GARCH) (0, 1) model provides the best description of return dynamics. Application of GARCH to daily stock returns of individual companies suggests that the companies illustrate high volatility for the period 2007–2009. Also, the returns from the portfolio of 20 companies reveal high volatility for the period 2007–2009. Hence, we prove that the Indian economy too has felt the impact of the global financial crisis. Finally, we conclude with some challenges for future research in this area.